Pengaruh Lingkungan Kerja, Nilai Sosial, Penghargaan Finansial dan Peran Dosen Terhadap Minat Berkarir di Perpajakan (Mahasiswa Akuntansi Akreditasi Unggul di Indonesia) - Susanti, Pipit; Prastyatini, Sri Lestari Yuli (Jurnal Ilmiah Global Education, 2025)
The study aims to analyze the influence of the work environment, social values, financial rewards, and the role of lecturers on students' career interests in the taxation sector. In the midst of globalization and rapid economic growth, it is essential to understand the factors that affect students' interest in pursuing a career in taxation. The methodology applied in this research is a survey with a quantitative approach and random sampling as a means to collect research data. Data collection was conducted through questionnaires distributed to students of accounting programs with excellent accreditation in Indonesia. There were 100 respondents from 18 universities in Indonesia. The data processing of the research results used IBM SPSS version 25. Data analysis was performed using multiple linear regression to determine the relationship between independent and dependent variables. The findings of the study indicate that a conducive work environment, high social values, and adequate financial rewards have a significant positive impact on students' interest in pursuing a career in taxation. Additionally, the role of lecturers as mentors and motivators has also been shown to contribute to enhancing students' career interests. The results of this research are expected to provide guidance for educational institutions and stakeholders in designing programs that support the career development of students in the taxation field.